Assessment of Genetic Diversity and Hybridization for the Endangered Conasauga Logperch (Percina jenkinsi) - Gregory R. Moyer; Anna L George; Patrick L. Rakes; J.R. Shute; Ashantye' S Williams (Southeastern Fishes Council Proceedings, 2015)
The Conasauga logperch, Percina jenkinsi is one of the rarest darters in North America afforded protection under the Endangered Species Act. Unfortunately, little is known about potential threats to the genetic diversity of this species, a narrow endemic. Loss of genetic diversity, spawning of closely related individuals, and hybridization with closely related congeners have been known to increase the rate of extinction for threatened or endangered taxa. We evaluated these risks by estimating and comparing levels of genetic diversity between P. jenkinsi and P. kathae (a closely related, morphologically similar, and more abundant congener) using twelve microsatellite loci. Specifically, we assessed whether a recent genetic bottleneck occurred in P. jenkinsi, determined the potential threat of hybridization between P. jenkinsi and P. kathae, and evaluated the maintenance of genetic diversity among P. jenkinsi collected in the wild, as broodstock for an experimental hatchery program, and their progeny. Estimates of genetic diversity between P. jenkinsi and P. kathae showed no significant differences in average number of alleles (7.083 vs. 9.5; P = 0.26), average observed heterozygosity (0.646 vs. 0.600, P = 0.64), or average expected heterozygosity (0.634 vs. 0.627, P = 0.86). Estimated Ne for P. jenkinsi and P. kathae was 114 (95% CI 60-526) and -497 (95% CI 264-infinity). We found no evidence of hybridization between P. jenkinsi and P. kathae and there was no detectable genetic signal of a recent genetic bottleneck in P. jenkinsi or P. kathae. Comparisons of observed and expected heterozygosity between P. jenkinsi collected in the wild, chosen as brood, and their progeny were similar; however, there was a 32% reduction in number of alleles (i.e., a loss of 16 of 50 alleles) due to hatchery influences. Specifically, twelve alleles (24% reduction) were lost between wild and hatchery broodstock, with the remainder being lost between hatchery brood and their respective offspring (note that the majority of alleles lost among groups were at observed frequencies < 0.05). Results of parentage analysis for hatchery P. jenkinsi showed that each male and female broodstock contributed offspring. The average number of offspring for the seven males and two females used as broodstock was 6.71 and 23.5. Based on the number of male and female broodstock, the predicted Ne of the offspring was 6.22 and by incorporating the mean and variance in progeny number, the observed Ne size was 4.97. The relatively high levels of genetic diversity coupled with the estimate of Ne indicated that the hatchery program was successful at minimizing the reduction in Ne between brood and progeny; however, the observed 32% loss of alleles between the wild P. jenkinsi and progeny of hatchery broodstock is alarming. This lost was due to sampling too few broodstock. Fortunately this loss can be mitigated should this program continue in the future by using larger broodstock collections over multiple years.
Keywords: reintroduction; captive breeding; conservation aquaculture; Percidae; darter